Synthesis and Characterization of some N-arylhydrazone and Imides derivatives from nalidixic acid - Shakyiar Lihimes, Hala; Abd Ail Abd Al Hussain, Hutham (Al-Qadisiyah Journal of Pure Science, 2018)
This research comprises the synthesizes of N-Arylhydrazone and Imides derivatives of Nalidixic acid were prepared by esterification of Nalidixic acid to form compound (1) then reacted with hydrazine hydrate 99% in ethanol to yield hydrazide derivative compound (2). The Schiff base (3a-3c) prepared from the corresponding aryl aldehydes with compound (2). Imides derivatives (4-6) were synthesized by reaction of compound (2) with appropriate anhydrides .The structures of compounds have been characterized by using some spectroscopic methods, 1HNMR and FT-IR.